2017
DOI: 10.3390/ijms18030662
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin MT1 and MT2 Receptors in the Ram Reproductive Tract

Abstract: Some melatonin functions in mammals are exerted through MT1 and MT2 receptors. However, there are no reports of their presence in the reproductive tract of the ram, a seasonal species. Thus, we have investigated their existence in the ram testis, epididymis, accessory glands and ductus deferens. Real-time polymerase chain reaction (qPCR) revealed higher levels of m-RNA for both receptors in the testis, ampulla, seminal vesicles, and vas deferens, than in the other organs of the reproductive tract (p < 0.05). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 64 publications
1
20
0
1
Order By: Relevance
“…Due to the complexity of melatonin catabolism, the knowledge about this process in the male reproductive tract is scarce. Our previous studies had confirmed both the presence of the melatonin synthesizing enzymes (Gonzalez‐Arto et al, ) and melatonin receptors (González‐Arto et al, ) in the ram reproductive tract. Therefore, our next step was to try to shed some light on the possible enzymatic catabolism of melatonin in these organs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Due to the complexity of melatonin catabolism, the knowledge about this process in the male reproductive tract is scarce. Our previous studies had confirmed both the presence of the melatonin synthesizing enzymes (Gonzalez‐Arto et al, ) and melatonin receptors (González‐Arto et al, ) in the ram reproductive tract. Therefore, our next step was to try to shed some light on the possible enzymatic catabolism of melatonin in these organs.…”
Section: Discussionsupporting
confidence: 64%
“…The melatonin main function is the regulation of seasonal sheep reproduction through the hypothalamus‐pituitary‐gonadal axis (Malpaux et al, ), although recent studies also suggest a direct action on sheep gametes and embryos, increasing their survival and quality (Abecia, Forcada, Casao, & Palacin, ; Cebrian‐Perez et al, ). Furthermore, we have detected the presence of melatonin‐synthesizing enzymes (Gonzalez‐Arto et al, ) and the melatonin receptors MT1 and MT2 in the testis and other organs of the ram reproductive tract (González‐Arto et al, ), as well as MT1 and MT2 receptors in ram spermatozoa (Casao et al, ). All these findings suggest the hypothesis that the ram testicular melatonin may protect spermatozoa from oxidative damage, as already has been suggested in other extrapineal organs (Acuña‐Castroviejo et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…MT1 and MT2 receptors are G protein-coupled receptors that are encoded by genes on human chromosome 4 and chromosome 11 [ 12 ]. Considering the functions of MT1 and MT2 receptors, apart from regulating the circadian rhythm, they are also responsible for different physiological functions, including reproduction, cardiovascular regulation, and immune function [ 13 , 14 , 15 , 16 ]. Melatonin is neuroprotective against the central nervous system (CNS) disorders, particularly the neurodegenerative diseases such as Parkinson’s and Alzheimer’s disease [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reproductive tissues in the male can produce melatonin, as demonstrated in ram [7]. These tissues would be able to respond to locally produced melatonin due to the presence of membrane receptors (MT1 and MT2) [8]. It also accumulates in secretions and other fluids such as the 2 of 20 seminal plasma [9][10][11] and the follicular fluid [12], affecting the physiology of the spermatozoon both within the male and the female.…”
Section: Introductionmentioning
confidence: 99%